Quality Attributes Demanded By Mobile App Stores On Mobile Apps Hosted On Their Platforms. - Kuria, Jane; Anselimo, Ikoha; Wabwoba, Frankline (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2022)
Mobile applications are designed and developed to run on a mobile device. The overwhelming adoption of mobile device technology, the rapid advancement of mobile devices and the significance of the Internet in today's society have shifted how businesses and consumers interact. The shift has subsequently upset mobile software programming enormously. The education sector has not been left behind on the adoption of mobile devices. For a mobile app to publication in an app store, the developers must meet the quality requirements of the store. To obtain the requirements, we surveyed four major app stores by leveraging the ISO/IEC 25010 quality standard to ensure the fulfillment of the quality requirements from the mobile app stores. We used the cross-sectional methodology strategy thus conducted the study within a limited time frame. Once an app is published in an app store, it becomes accessible to the entire universe of users. Mobile app developers should be familiar with the quality control requirements to develop acceptable apps. The purpose of this paper was to survey and identify the most relevant quality requirements set up by mobile applications The study found, Usability, Performance, Maintainability and Support categories were the most important